2023
DOI: 10.3390/foods12061330
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Biostarter Effect on the Quality of Dry-Aged Beef

Abstract: Meat aging is a process consisting of its storage in specific conditions which leads to an increase in its organoleptic qualities. The most common method of meat aging is the wet vacuum-bag based method, whereas the traditional method, called dry-aging, involves keeping meat at a low temperature for an extended time. However, this process is characterized by low repeatability of the results. Therefore, different approaches to stabilize the process are tested. The aim of this study was to analyze the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, the level of acceptability of the developed culinary recipes was determined through sensory analysis. Four standard recipes were evaluated, representing the different maturation times (28,32,42, and 45 days), the meat cuts, and the sous-vide cooking technique. See Figure 5.…”
Section: Standardization Of Matured Sous Vide Beef Recipesmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the level of acceptability of the developed culinary recipes was determined through sensory analysis. Four standard recipes were evaluated, representing the different maturation times (28,32,42, and 45 days), the meat cuts, and the sous-vide cooking technique. See Figure 5.…”
Section: Standardization Of Matured Sous Vide Beef Recipesmentioning
confidence: 99%
“…Several studies have shown that dry-aged beef is characterized by better flavor, odor, and taste. It is also often considered to have more favorable palatability, with stronger notes of meaty, roast meat, and brown roast meat, as well as scoring higher for umami, buttery, caramelized, sweet, and nutty flavors [42].…”
Section: Dry Aging Process For Bone-in Beefmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of the muscle proteins SDS−PAGE was performed to determine the raw muscle protein profile and after heat treatment following the method of Przybylski et al [55] using a Bio−Rad apparatus. A sample of 20 mg meat was homogenized at 13,500 rpm (IKA DI 25 Ultra Turrax, Königswinter, Germany) with 600 µL of 0.003 M phosphate buffer at pH 7 for 1 min.…”
Section: Profile Of the Muscle Proteinsmentioning
confidence: 99%
“…The Changes in the protein profile and protein degradation during aging, marinating and after heat treatment are valuable markers of meat quality, especially its tenderness [55,[101][102][103][104].…”
Section: Sensory Attribute and Definitionmentioning
confidence: 99%